Tooth fractures in the Krapina Neandertals. Issue 123 (October 2018) - Belcastro, Maria Giovanna; Mariotti, Valentina; Riga, Alessandro; Bonfiglioli, Benedetta; Frayer, David W.
Abstract: Dental fractures can be produced during life or post-mortem. Ante-mortem chipping may be indicative of different uses of the dentition in masticatory and non-masticatory activities related to variable diets and behaviors. The Krapina collection (Croatia, 130, 000 years BP), thanks to the large number of teeth (293 teeth and tooth fragments) within it, offers an excellent sample to investigate dental fractures systematically. Recorded were the distribution, position and severity of the ante-mortem fractures according to standardized methods. High frequencies of teeth with chipping in both Krapina adults and subadults suggest that the permanent and deciduous dentition were heavily subjected to mechanical stress. This is particularly evident when the frequencies of chipping are compared with those in modern humans (Upper Paleolithic and historic samples) that we analysed using the same methods. The distribution of chipping in the Krapina sample (anterior teeth are more affected) and its position (labial) suggest a systematic use of the anterior teeth for non-masticatory tasks.